Beyond Dualism Agricultural Productivity, Small Towns, and Structural Change in Bangladesh - Emran, M Shahe (The World Bank, 2017)
This paper uses a framework that goes beyond rural-urban dualism and highlights the role of small town economy in understanding structural change in a developing country. It provides a theoretical and empirical analysis of the role of agricultural productivity in structural transformation in the labor market. The empirical work is based on a general equilibrium model that formalizes the demand and labor market linkages: the small-town draws labor away from the rural areas to produce goods and services whose demand may depend largely on rural income. The theory clarifies the role played by the income elasticity of demand and the wage elasticity with respect to productivity increase in agriculture. For productivity growth to lead to a demand effect, the wage elasticity has to be lower than a threshold. When the demand for goods and services produced in small towns comes mainly from the adjacent rural areas, the demand effect can outweigh the negative wage effect, and lead to higher employment in the town-goods sector. Using rainfall as an instrument, the empirical analysis finds a significant positive effect of agricultural productivity on rice yield and agricultural wages. Productivity shock increases wages more in the rural sample compared with the small town economy sample, but structural change in employment is more pronounced in the small-town economy. In the rural sample, it increases employment only in small-scale manufacturing and services. In contrast, a positive productivity shock has large and positive impacts on employment in construction and transport, education, health and other services, and manufacturing employment in larger scale enterprises located in small towns and cities. Agricultural productivity growth induces structural transformation within the services sector in small towns, with employment in skilled services growing at a faster pace than that of low skilled services